Rifaximin‐altered gut microbiota components associated with liver/neuropsychological functions in patients with hepatic encephalopathy: An exploratory data analysis of phase II/III clinical trials. Issue 4 (1st February 2019) - Kawaguchi, Takumi; Suzuki, Fumitaka; Imamura, Masatoshi; Murashima, Naoya; Yanase, Mikio; Mine, Tetsuya; Fujisawa, Masaki; Sato, Ikuya; Yoshiji, Hitoshi; Okita, Kiwamu; Suzuki, Kazuyuki
Abstract : Aims: Rifaximin (RFX), a non‐systemic antibiotic, improves liver/neuropsychological functions in patients with hepatic encephalopathy (HE). We aimed to investigate the clinical profiles associated with gut bacterial loads using exploratory data analysis and the effects of RFX on the gut microbiota of patients with HE. Methods: We analyzed the data from 17 patients with HE who underwent fecal microbiota examination in phase II/III trials in Japan. Profiles associated with genera Streptococcus, Veillonella, and Lactobacillus loads were analyzed using classification and regression trees (CART). Changes in gut microbial consortia of seven patients with HE were then assessed 2 weeks after RFX treatment by principal component analysis. Results: In the CART, the first and second divergence variables for each higher bacterial load were as follows: (i) in Streptococcus, the number connection test‐A ≥39.55 s and presence of portal‐systemic shunt; (ii) in Veillonella, serum potassium levels <4.75 mEq/L and total cholesterol level <129.5 mg/dL; and (iii) in Lactobacillus, white blood cell counts ≥3.4 × 10 3 /μL and aspartate aminotransferase level ≥44.5 U/L. There was no significant change in total bacterial load before and after RFX treatment; however, there was a decrease in Streptococcus, Veillonella, and Lactobacillus counts after RFX treatment. Conclusion: We report clinical profiles associated with gut bacterial loads in patients with HE, and showed that RFX altered gut microbiota components associated with liver/neuropsychological functions. Thus, RFX could improve liver/neuropsychological functions through the regulation of the gut microbial consortia in patients with HE.